Exploring The Drivers of Impulse Buying Behavior on Shopee Live Audiences - Steffani; Moses Hutabarat (International Journal of Economics Accounting and Management, 2025)
This research aims to analyze the factors influencing impulse buying behavior among Shopee Live audiences. The study explores various factors, including Impulse Buying Tendency, Shopping Enjoyment Tendency, Consumer Mood, Product Attributes, Website Quality, Marketing Stimuli, and Social Influence, and their effects on impulsive purchasing behavior. Data were collected from 194 respondents using an online survey, with purposive sampling, and analyzed through PLS-SEM (Partial Least Squares Structural Equation Modeling). The findings reveal that Impulse Buying Tendency, Consumer Mood, and Marketing Stimuli significantly influence impulse buying behavior, while Shopping Enjoyment Tendency, Product Attributes, Website Quality, and Social Influence do not have a significant effect. These results offer valuable insights for platform operators, marketers, and sellers aiming to optimize strategies on Shopee Live and similar platforms to boost impulse buying behavior.